2005
DOI: 10.1021/es0484754
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Decomposition of Environmentally Persistent Perfluorocarboxylic Acids by Use of Persulfate as a Photochemical Oxidant

Abstract: Photochemical decomposition of persistent perfluorocarboxylic acids (PFCAs) in water by use of persulfate ion (S2O8(2-)) was examined to develop a technique to neutralize stationary sources of PFCAs. Photolysis of S2O8(2-) produced highly oxidative sulfate radical anions (SO4-), which efficiently decomposed perfluorooctanoic acid (PFOA) and other PFCAs bearing C4-C8 perfluoroalkyl groups. The major products were F- and CO2; also, small amounts of PFCAs with shorter than initial chain lengths were detected in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
262
4
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 518 publications
(289 citation statements)
references
References 34 publications
13
262
4
4
Order By: Relevance
“…The formation of formic acid indicated that the C C bond between C 7 F 15 and COOH may be cleaved firstly during PFOA decomposition. Hori et al [22,23] pointed out that CO 2 was identified in the gas phase when photochemical decomposition of PFOA under the condition of 0.48 MPa oxygen gas. In the present study, the reaction was conducted in an open system, and any possible products in the gas phase such as CO 2 were not determined.…”
Section: Effect Of Fe (Iii) On Photochemical Decomposition Of Pfoamentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of formic acid indicated that the C C bond between C 7 F 15 and COOH may be cleaved firstly during PFOA decomposition. Hori et al [22,23] pointed out that CO 2 was identified in the gas phase when photochemical decomposition of PFOA under the condition of 0.48 MPa oxygen gas. In the present study, the reaction was conducted in an open system, and any possible products in the gas phase such as CO 2 were not determined.…”
Section: Effect Of Fe (Iii) On Photochemical Decomposition Of Pfoamentioning
confidence: 99%
“…H 3 PW 12 O 40 [22] or by using persulfate ion (S 2 O 8 2− ) [23] as photochemical oxidant under UV-vis light irradiation (220-460 nm) in the presence of oxygen gas. On the other hand, Zhang et al [24,25] investigated the influences of oxidant (K 2 S 2 O 8 ), reaction atmospheres (O 2 , N 2 ) and UV light (185 nm and 254 nm light) on PFOA decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, UV/S 2 O 8 2-process has been confirmed to be effective in degrading organic contaminants (Hori et al 2005(Hori et al , 2007Lau et al 2007;Salari et al 2009;Criquet and Leitner 2009;Lin et al 2011). For example, Lin et al (2011) found that phenol (0.5 mM) can be completely degraded within 20 min using UV/S 2 O 8 2-process with a UV wavelength of 254 nm and an S 2 O 8 2-concentration of 84 mM.…”
Section: Introductionmentioning
confidence: 99%
“…The indirect photoreactions have been developed to improve the efficiency of photo degradation. Some oxidants, such as ozone (Lin et al, 2012a), persulfate (Hori et al, 2005) and ferric ion (Hori et al, 2007), have been found to enhance the degradation and mineralization of PFOA. However, these methods require chemical compounds that are potential secondary pollutants.…”
Section: Introductionmentioning
confidence: 99%